The Effect of a tool for helping the learning of forehand and backhand stroke in tennis for ages (10-15) - Raed, Hasan; Laith, Khlood (Journal of Physical Education, 2022)
the study aimed to manufacture a tool to learn the forehand and backhand stroke in tennis and recognize its effect on learning the two skills, the researcher assumed that were significant differences between the post-test between the experimental and control group. The researchers used the experimental approach in the style of experimental and control groups. The subject was (16) players of beginner’s trainees aged (10-15) at Al-Jadriya Tennis Academy. The subject was distributed randomly into two equal groups of (6) players in each one, in addition to (4) players who were excluded because they didn’t adhere to the training. The researchers concluded that using the tool contributed to learning the forehand and backhand stroke and the varied and continuous repetition of the exercises by using the tool increased the players’ motivation toward better development in skill performance.